Fluid mechanics laboratory as a teaching tool - Bolaños, Fabio (Ingeniería Solidaria, 2012)
The author explains how teaching and knowledge appropriation of fluid mechanics can be greatly improved when the students attain the solution or explanation of physical phenomena in the laboratory, working from situations or problems based on experiments. With this educational point of view, the author presents the results of the research project: “Design of a laboratory for the fluid mechanics course, as a teaching tool for the industrial engineering program of the Universidad Cooperativa de Colombia, Pasto branch”, carried out in 2006. The paper shows how the laboratory guides used for the project were elaborated and the benefits they bring; among them is the application of theoretical knowledge by fourth semester students to solve real problems. The practices of the proposed laboratories gave the students a significant understanding of physics.